Selisik Leluhur Lagu Anak Sunda Untuk Prestasi Belajar Siswa - Hendy Yuliansyah (Pascasarjana ISBI Bandung, 2017)
A song is one of the universal human products. As the work of art, a folk song is rarely appreciated by the public. However, it saves signifcance which can certainly be applied for the beneft of education. The research tries to disclose three children Sundanese songs, they are, ucang-ucang angge, cing caripit kajapit, and oray-orayan. The lyrics and the song embody the creativity that can help children learning. Although not directly related to religious teachings, this song becomes a good stimulus for the students to be consistent in learning.Keyword: Culture, Creativity, Song, Work of Art